A study of copolymerization with 4-bromobenzyl methacrylate and ethyl methacrylate - Coskun, MF; Erol, I; Demirelli, K; Coskun, M (Marcel Dekker Inc, 2002)
4-Bromobenzyl methacrylate [BrBMA] monomer was synthesized from a reaction of sodium methacrylate with 4-bromobenzylbromide. The copolymerization of this monomer with ethyl methacrylate (EMA) and its homopolymerization were carried out in a 1,4-dioxane solution at 60degreesC using 2,2'-azobisisobutyronitrile [AIBN] as initiator. The monomer and the polymers were characterized by IR, H-1 and C-13-NMR techniques. The composition or monomeric units in the copolymer system was calculated using H-1-NMR spectroscopy by comparing the integral values of well separated aromatic and aliphatic proton peaks. The monomer reactivity ratios of copolymerization were determined by using the Kelen-Tudos (K-T), Inverted Fineman-Ross (IFR) and Yezrielev-Brokhina-Roskin (YBR) methods, and were found to be r(1) = 0.44, r(2) = 0.63 and r(1) = 0.24, r(2) = 0.47 and r(1) = 0.37, r(2) = 0.64, respectively (r(1) is the monomer reactivity ratio of BrBMA). Based on the experimental data of the K-T method, triad analysis was performed. It is concluded that this copolymerization results in statistical-type macromolecules. The solubility parameters and the glass transition temperature of the copolymers were determined as a function of copolymer composition.
Keywords: monomer reactivity ratios; ethylmethacrylate